Use of glycosylated HbA1c and random blood sugar as a screening tool for gestational diabetes mellitus in first trimester - Amreen, Shaiesta; Suneel, Anjali; Shetty, Ananya; Vasudeva, Akhila; Kumar, Pratap (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: GDM cases go unidentified with inadequate screening methods in first trimester which in turn increases the maternal and neonatal morbidity which is preventable. The purpose of the study was to find out a cut off level for HbA1c and RBS at first trimester for screening Gestational diabetes mellitus (GDM). Methods: Observational study on pregnant women in a tertiary care teaching institution. Early screening with HbA1c and RBS at booking visit and followed up to second trimester GTT at 24-28 weeks. Pregnant women were divided into 2 groups based on GTT results. Pregnant women with overt diabetes and multiple pregnancy were not included in the study. Results: Out of the 151 subjects, 76 cases were diagnosed with GDM while the other 75 were found to be non-GDM by following the 75g GTT approved by IADPSG. According to our study optimal cut-off for HbA1C was found to be 5.496±0.48 %, as it gives a sensitivity of 80% and specificity of 55.3%. Optimal cut-off for RBS was found to be 112±0.77 mg/dl, as it gives a sensitivity of 35.55 and specificity of 94.7%. Conclusions: Glyco Hb A1c and RBS can be used as screening tool for the diagnosis of GDM. The likelihood of having GDM at a cutoff of Glyco HbA1c 5.5% is 1.8 times and RBS level 112mg/dl is 7 times in pregnant women.